Stability of clonidine hydrochloride in an oral powder form compounded for pediatric patients in Japan - Jumpei Saito; Takehisa Hanawa; Takahiro Matsumoto; Nozomi Yoshikawa; Tsutomu Harada; Kana Iwahashi; Hidefumi Nakamura; Akimasa Yamatani (BMC, 2021)
Abstract Background Clonidine hydrochloride is used to treat sedative agent withdrawals, malignant hypertension, and anesthesia complications. Clonidine is also prescribed off-label to pediatric patients at a dose of 1 μg/kg. The commercially available enteral form of clonidine, Catapres® tablets, is often compounded into a powder form by pharmacists to achieve dosage adjustments for administration to pediatric patients. However, the stability and quality of compounded clonidine powder have not been verified. The objectives of this study were to formulate a 0.2 mg/g oral clonidine hydrochloride powder and assess the stability and physical properties of this compounded product in storage. Methods A 0.2 mg/g clonidine powder was prepared by adding lactose monohydrate to crushed and filtrated clonidine tablets. The powder was stored in polycarbonate amber bottles or coated paper packages laminated with cellophane and polyethylene. The stability of clonidine at 25 °C ± 2 °C and 60% ± 5% relative humidity was examined over a 120-d period in "bottle (closed)," "bottle (in use)," and "laminated paper" storage conditions. Drug dissolution and powder X-ray diffraction analysis were conducted to assess physicochemical stabilities. Validated liquid chromatography-diode array detection was used to detect and quantify clonidine and its degradation product, 2,6-dichloroaniline (2,6-DCA). Results Clonidine content was maintained between 90.0 and 110.0% of the initial contents in all packaging and storage conditions. After 120 d of storage, 2,6-DCA was not detected, and no crystallographic and dissolution changes were observed. Conclusions Compounded clonidine powder stability was maintained for 120 d at 25 °C ± 2 °C and 60% ± 5% relative humidity. This information may contribute to the management of clonidine compounded powder in community and hospital pharmacies in Japan.